Mimi the laughter fairy - Meadows, Daisy (London : Orchard Books, 2016)
Everyone knows Kirsty and Rachel are best friends. But when Jack Frost steals the Friendship Fairies' magical objects, the special bond of BFFs everywhere is at risk! Can they fight the Ice Lord and his goblin minions to restore the magic of friendship in both the Fairyland and worlds?
5+.
Keywords: Fairies -- Juvenile fiction; Magic -- Juvenile fiction; Fantasy fiction